Interdependence and contagion in global asset markets - John Beirne; Jana Gieck (European Central Bank (ECB), 2012)
This paper provides an empirical assessment of interdependence and contagion across three asset classes (bonds, stocks, and currencies) for over 60 economies over the period 1998 to 2011. Using a global VAR, we test for changes in the transmission mechanism – both within and cross-market changes - during periods of turbulence in financial markets. Our results suggest that within-market effects over the sample period for each asset market are highly significant for advanced economies. For emerging economies, these within-market effects mostly apply to the equity market. Contagion effects within-market are most notable in Latin America and Emerging Asia for equities. Cross-market contagion is identified from global bonds to local stocks in Central and Eastern Europe, but from global stocks to domestic bonds in the case of advanced economies. Impulse responses indicate that in crisis times, the origin of the shock plays an important role on the nature of the global transmission. The evidence suggests that in times of financial crisis, shocks that emanate in the US, particularly equity shocks, lead to risk aversion by investors in equities and currencies globally and in some emerging market bonds. Euro area shocks tend to have the most significant effect within the bond market. Our results have implications for policymakers in terms of understanding financial exposures and vulnerabilities and for investors in relation to portfolio rebalancing and the construction of portfolio diversification strategies across asset classes in crisis and non-crisis times.
Keywords: F30; G15; 330; asset markets; Contagion; Global VAR